Genetic relationship between Na-rich chondrules and Ca, Al-rich inclusions? – Formation of Na-rich chondrules by melting of refractory and volatile precursors in the solar nebula. (15th March 2016) - Ebert, Samuel; Bischoff, Addi
Abstract: Al-rich objects (Ca, Al-rich inclusions (CAIs), Al-rich chondrules, Al-rich fragments) occur in all chondrite classes. These objects can be centimeter-sized in CV3 carbonaceous chondrites, but they are generally much smaller in other chondrite groups and classes. Within the ordinary chondrites, most Al-rich objects are chondrules that vary from Ca- to Na-rich. Here, we have investigated the mineralogy and major element chemistry of 32 Na-rich chondrules and 3 Na-rich fragments from 15 different chondrites. Most objects (chondrules and chondrule fragments) are from ordinary chondrites (petrologic types 3.2–3.8), but two of the chondrules are from two CO3 chondrites, and three of the chondrules are from one Rumuruti (R)-chondrite. We found that these Na-rich objects have bulk Na2 O-concentrations between 4.3 and 15.2 wt%. Texturally, they typically consist of euhedral to subhedral (often skeletal) mafic minerals (olivine and pyroxenes) embedded within a nepheline-normative, glassy mesostasis, which is brownish in transmitted light. In addition, some chondrules contain euhedral to subhedral spinel. Bulk chondrule compositions show group II, group III, and ultrarefractory rare earth element (REE) patterns similar to those found in CAIs. These results clearly demonstrate that the Na-rich chondrules must have been formed by melting of precursors containing an (ultra-)refractory element-rich component and Na-rich constituents. The Na-rich chondrules showed Sm and Eu anomalies, indicating that they must have formed at low oxygen fugacities. Based on the chemical composition of the Na-rich objects, we can rule out that they were formed as a result of planetary formation due to metasomatic processes or processes related to collisions between molten planetesimals.